A compendium on maternal mortality research in Bangladesh - Akhtar, Halida Hanum; Bangladesh Institute of Research for Promotion of Essential & Reproductive Health and Technologies (Dhaka : Bangladesh Institute of Research for Promotion of Essential & Reproductive Health and Technologies, 1998)
Contributed articles.
"Dhaka, November 1998."
Includes bibliographical references (page iii).
Keywords: Mothers -- Mortality -- Bangladesh; Health services accessibility -- Bangladesh